Factors associated with clinical inertia in type 2 diabetes mellitus patients treated with metformin monotherapy. (2nd December 2019) - Kartoun, Uri; Iglay, Kristy; Shankar, R. Ravi; Beam, Andrew; Radican, Larry; Chatterjee, Arnaub; Pai, Jennifer K.; Shaw, Stanley
Abstract: Aims: To assess demographic and clinical characteristics associated with clinical inertia in a real-world cohort of type 2 diabetes mellitus patients not at hemoglobin A1c goal (<7%) on metformin monotherapy. Methods: Adult (≥18 years) type 2 diabetes mellitus patients who received care at Massachusetts General Hospital/Brigham and Women's Hospital and received a new metformin prescription between 1992 and 2010 were included in the analysis. Clinical inertia was defined as two consecutive hemoglobin A1c measures ≥7% ≥3 months apart while remaining on metformin monotherapy (i.e. without add-on therapy). The association between clinical inertia and demographic and clinical characteristics was examined via logistic regression. Results: Of 2848 eligible patients, 43% did not achieve a hemoglobin A1c goal of <7% 3 months after metformin monotherapy initiation. A sub-group of 1533 patients was included in the clinical inertia analysis, of which 36% experienced clinical inertia. Asian race was associated with an increased likelihood of clinical inertia (OR = 2.43; 95% CI = 1.48–3.96), while congestive heart failure had a decreased likelihood (OR = 0.58; 95% CI = 0.32–0.98). Chronic kidney disease and cardiovascular/cerebrovascular disease had weaker associations but were directionally similar to congestive heart failure. Conclusions: Asian patients were at an increased risk of clinical inertia, whereas patients with comorbidities appeared to have their treatment more appropriately intensified. A better understanding of these factors may inform efforts to decrease the likelihood for clinical inertia.